Modelagem matemática e comportamento dinâmico da suspensão passiva de um pulverizador agrícola autopropelido - Ferreira, André Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
This paper is based on the elaboration of mathematical suspension models which can evaluate performance parameters of an agricultural vehicle based on the vibration caused by irregularities on the soil surface. In this paper, these irregularities are represented by step input, sine input and obstacles of leveled road according to ISO 5008 specifications. The motion equations are obtained from the mathematical models of a quarter car and half car. Numerical simulations are performed on Matlab®, Simulink® and Visual Nastran®. Based on known input, characteristics of suspension elements can be determined in order to obtain desired levels of comfort and safety. Different system configurations were analyzed changing the stiffness ratio and the damping coefficient based on a standard model. Results were treated statistically and compared among themselves. It was verified that the increase in stiffness ratio results in the reduction of the vertical acceleration and in the increase of the suspension travel, improving comfort but reducing safety. On the other hand, the reduction of damping coefficient causes the reduction of vertical acceleration up to a certain point, and from this point on the acceleration increases again. The suspension travel, however, reduces as damping coefficient is reduced.

O trabalho é baseado na elaboração de modelos matemáticos de suspensão que permitem avaliar parâmetros de desempenho de um veículo agrícola em função da excitação provocada pelas irregularidades do solo. Neste trabalho, estas irregularidades são representadas por entrada degrau, entrada seno e obstáculos de uma pista normalizada segundo a norma ISO 5008. As equações do movimento são obtidas a partir dos modelos matemáticos de um quarto de veículo e meio veículo. As simulações numéricas são executadas nos softwares Matlab®, Simulink® e Visual Nastran®. A partir da entrada conhecida, podem-se determinar as características dos elementos da suspensão para obter níveis desejáveis de conforto e segurança. Foram analisadas diferentes configurações do sistema, variando-se a relação de rigidez e a constante de amortecimento equivalente a partir de um modelo considerado padrão. Os resultados foram tratados estatisticamente e comparados entre si, verificando-se que o aumento da relação de rigidez resulta na redução da aceleração vertical e no aumento do curso da suspensão, melhorando o conforto e diminuindo a segurança. Por outro lado, a redução do amortecimento provoca a redução da aceleração vertical até um determinado ponto e, a partir deste, a aceleração volta a crescer. Já o curso da suspensão diminui à medida que o amortecimento é reduzido.
Keywords: Agricultural machines; Agricultural sprayer; Passive suspension; Numerical simulations; Máquinas agrícolas; Pulverizador agrícola; Suspensão passiva; Simulações numéricas